Exploring EFL Students’ Perceptions of the Use of English Video in Learning Writing - Adristi Jauza Heditami; Suciana Wijirahayu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Writing is often regarded as one of the most challenging skills for students learning English as a foreign language (EFL). This study looks into how EFL students feel about using English videos in their writing classes. A combination of methods was used in a specific order, including a questionnaire with rating scales, watching classes to observe what happens, and having conversations with open-ended questions. The results indicate that students generally have positive perceptions of the use of video in learning. Using videos in English was found to help students feel more motivated, confident, and involved in their writing tasks. Videos also helped students understand writing topics better, come up with ideas, and arrange their thoughts in a clearer way. Videos helped make writing clearer and more detailed by offering visual and contextual support. In general, using videos in lessons helps create a more interesting, significant, and focused learning environment for students when teaching writing in English as a foreign language.